2015
DOI: 10.1016/j.tibs.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Axonal Transport by Protein Kinases

Abstract: The intracellular transport of organelles, proteins, lipids, and RNA along the axon is essential for neuronal function and survival. This process, called axonal transport, is mediated by two classes of ATP-dependent motors, kinesins, and cytoplasmic dynein, which carry their cargoes along microtubule tracks. Protein kinases regulate axonal transport through direct phosphorylation of motors, adapter proteins, and cargoes, and indirectly through modification of the microtubule network. The misregulation of axona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 113 publications
2
102
0
Order By: Relevance
“…In support, biochemical approaches illuminated multiple pathways promoting the detachment of conventional kinesin from membranes [76,100]. Further, cumulative data indicates that phosphorylation represents a major mechanism for the regulation of conventional kinesin-based AT [28,42,58]. Many findings supporting this concept were initially established using isolated squid axoplasm, a model that greatly facilitates the evaluation of axon-autonomous molecular events [49,94].…”
Section: Functional Implications Of Conventional Kinesin Subunit Varimentioning
confidence: 97%
See 1 more Smart Citation
“…In support, biochemical approaches illuminated multiple pathways promoting the detachment of conventional kinesin from membranes [76,100]. Further, cumulative data indicates that phosphorylation represents a major mechanism for the regulation of conventional kinesin-based AT [28,42,58]. Many findings supporting this concept were initially established using isolated squid axoplasm, a model that greatly facilitates the evaluation of axon-autonomous molecular events [49,94].…”
Section: Functional Implications Of Conventional Kinesin Subunit Varimentioning
confidence: 97%
“…However, these diseases are not associated with mutations in conventional kinesin or other KIFs, so other mechanisms are thought to underlie these deficits. Interestingly, abnormal activation of protein kinases and aberrant patterns of protein phosphorylation represent pathogenic hallmarks common to most neurodegenerative diseases [28,104], and many kinases deregulated in these diseases have been implicated in the regulation of conventional kinesin-based AT. In the context of HD, mutant huntingtin has been shown to inhibit AT through a mechanism involving JNK3 activation and phosphorylation of KIF5s [78].…”
Section: Functional Implications Of Conventional Kinesin Subunit Varimentioning
confidence: 99%
“…Studies have shown that MTs serve as tracks, which work in concert with proteins kinases and motor proteins (e.g., dynein, kinesins), for the transport of cell organelles, such as endocytic vesicles, mitochondria, lipids, proteins and others, across cell cytosol in response to changes in cell environment or external cues. [14][15][16] For instance, cytoplasmic dynein complex (CDC) and kinesin-14 family members are the only 2 motor proteins utilizing energy release from hydrolysis of ATP in mammalian cells known to move their cargoes to the minus-end and plus-end directionally, respectively 17 ( Fig. 1B-E; Fig.…”
Section: Role Of Microtubule (Mt)-based Cytoskeletonmentioning
confidence: 99%
“…It has been proposed that F-actin at the apical ES serves as the vehicle to transport germ cells [17]. Earlier studies on the microtubule cytoskeleton in the seminiferous epithelium propose that microtubules serve as the tracks for germ cells to be transported and involving microtubule-specific motor proteins such as kinesin [1821], analogous to the function of microtubules to serve as the tracks in other mammalian epithelia [22]. Herein, we discuss the roles of the microtubule cytoskeleton in germ cell development and transport.…”
Section: Introductionmentioning
confidence: 99%